Fuel characteristics and trace gases produced through biomass burning - BAMBANG HERO SAHARJO; SHIGETO SUDO; SEIICHIRO YONEMURA; HARUO TSURUTA (Biodiversitas Journal of Biological Diversity, 2010)
Saharjo BH, Sudo S, Yonemura S, Tsuruta H (2010) Fuel characteristics and trace gases produced through biomass burning. Biodiversitas 11: 40-45. Indonesian 1997/1998 forest fires resulted in forest destruction totally 10 million ha with cost damaged about US$ 10 billion, where more than 1 Gt CO2 has been released during the fire episode and elevating Indonesia to one of the largest polluters of carbon in the world where 22% of world’s carbon dioxide produced. It has been found that 80-90% of the fire comes from estate crops and industrial forest plantation area belongs to the companies which using fire illegally for the land preparation. Because using fire is cheap, easy and quick and also support the companies purpose in achieving yearly planted area target. Forest managementand land use practices in Sumatra and Kalimantan have evolved very rapidly over the past three decades. Poor logging practices resulted in large amounts of waste will left in the forest, greatly elevating fire hazard. Failure by the government and concessionaires to protect logged forests and close old logging roads led to and invasion of the forest by agricultural settlers whose land clearances practices increased the risk of fire. Several field experiments had been done in order to know the quality and the quantity of trace produced during biomass burning in peat grass, peat soil and alang-alang grassland located in South Sumatra, Indonesia. Result of research show that different characteristics of fuel burned will have the different level also in trace gasses produced. Peat grass with higher fuel load burned produce more trace gasses compared to alang-alang grassland and peat soil.Key words: peat soil, peat grass, alang-alang, biomass burning, trace gas.